2019
DOI: 10.1111/cyt.12705
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum of cytomorphological features of extranodal NK/T‐cell lymphoma, nasal type

Abstract: Objective: Extranodal natural killer/T-cell lymphoma, nasal type (ENKTL) is an aggressive extranodal lymphoma of NK-cell or T-cell lineage. Its clinical features overlap with those of several sinonasal mass lesions. While the histopathological features are well described, diagnosis is often difficult, owing to presence of extensive coagulative necrosis, so that repeated biopsies may sometimes be necessary for correct diagnosis. Literature on cytological findings of ENKTL is limited. Methods: Cytomorphological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 22 publications
(51 reference statements)
0
14
0
Order By: Relevance
“…To date, there are only a handful of reported cases with very limited data on the cytological features. [8][9][10][11][12][13][14][15][16][17] In this study of four new cases of effusion ENKTL, we found that the neoplastic cells were frequently of large to anaplastic morphology with azurophilic granules.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…To date, there are only a handful of reported cases with very limited data on the cytological features. [8][9][10][11][12][13][14][15][16][17] In this study of four new cases of effusion ENKTL, we found that the neoplastic cells were frequently of large to anaplastic morphology with azurophilic granules.…”
Section: Discussionmentioning
confidence: 99%
“…ENKTL rarely involves pleural effusion or ascites, which may occur at disease progression. In the literature, there are only a few cases of ENKTL with lymphomatous effusions . Herein we report four new cases of effusion ENKTL and the results of literature review, focusing on the cytopathological features, immunophenotype, and cellular lineage in terms of T‐vs NK‐cell origin.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…The cytological diagnosis of two different types of T cell malignancies is discussed in the two papers by Kanwalpreet et al and Kobata et al . The former is a retrospective analysis of histologically confirmed cases of extranodal nasal type NK/T cell lymphomas.…”
mentioning
confidence: 99%